African identity : the study of Zakes Mda 's Madonna of excelsior and Bessie Head's Maru - Mahasha, Thabo Widley (My University, 2014)
This study discusses African identity as portrayed in Zakes Mda’s The Madonna of Excelsior (2002) and Bessie Head’s Maru (1971). It explores identity and its subcomponents within the South African context as asserted in these novels. Mda employs a retrospective communal voice that blends historical accounts with fiction in order to subvert and satirise apartheid nationalism. Head, on the other hand, constructs a positive image of feminine identity in the world characterised by tribalism, patriarchal system and stereotypical subjugation of women. She dismantles established racial and ethnic prejudice against minority groups and the underprivileged. The study applies a trilogy of theoretical framework to analyse and interpret selected data: Discourse Analysis, Text Analysis and Afrocentricity. It further examines a fluidity of identities in both social and political spheres and demonstrates how suppression of these identities affects individuals and nation states. It reveals that, as a microcosm of Africa, South Africa reflects atrocious injustices of the past, carried out in the form of colonisation and apartheid, bringing about a different kind of identity of the African people. These two novels take us back to the past so that we can understand the present and subsequently build Africa’s identity of the future. KEY CONCEPTS Afrocentricity; Identity; Discrimination; Miscegenation; Otherness; Hybridity; Animalistic Dehumanisation.
Thesis (M.A. (English Studies)) -- University of Limpopo, 2014
Keywords: Afrocentricity; Discrimination; South African literature (Black authors) -- History and criticism.; Apatheid in literature.; Politics in literature.; Mda Zakes -- Criticism and interpretation.; Head Bessie -- Criticism and interpretation.; Afrocentrism.